Exploring Ovarian Cancer Cell Resistance to Rhenium Anticancer Complexes. (27th May 2020) - Marker, Sierra C.; King, A. Paden; Swanda, Robert V.; Vaughn, Brett; Boros, Eszter; Qian, Shu‐Bing; Wilson, Justin J.
Abstract: Rhenium tricarbonyl complexes have been recently investigated as novel anticancer agents. However, little is understood about their mechanisms of action, as well as the means by which cancer cells respond to chronic exposure to these compounds. To gain a deeper mechanistic insight into these rhenium anticancer agents, we developed and characterized an ovarian cancer cell line that is resistant to a previously studied compound [Re(CO)3 (dmphen)(ptolICN)] +, where dmphen=2, 9‐dimethyl‐1, 10‐phenanthroline and p tolICN= para ‐tolyl isonitrile, called TRIP. This TRIP‐resistant ovarian cancer cell line, A2780TR, was found to be 9 times less sensitive to TRIP compared to the wild‐type A2780 ovarian cancer cell line. Furthermore, the cytotoxicities of established drugs and other rhenium anticancer agents in the TRIP‐resistant cell line were determined. Notably, the drug taxol was found to exhibit a 184‐fold decrease in activity in the A2780TR cell line, suggesting that mechanisms of resistance towards TRIP and this drug are similar. Accordingly, expression levels of the ATP‐binding cassette transporter P‐glycoprotein, an efflux transporter known to detoxify taxol, were found to be elevated in the A2780TR cell line. Additionally, a gene expression analysis using the National Cancer Institute 60 cell line panel identified the MT1E gene to be overexpressed in cells that are less sensitive to TRIP. Because this gene encodes for metallothioneins, this result suggests that detoxification by this class of proteins is another mechanism for resistance to TRIP. The importance of this gene in the A2780TR cell line was assessed, confirming that its expression is elevated in this cell line as well. As the first study to investigate and identify the cancer cell resistance pathways in response to a rhenium complex, this report highlights important similarities and differences in the resistance responses of ovarian cancer cells to TRIP and conventional drugs. Abstract : TRIPping up resistance ! A rhenium‐resistant ovarian cancer cell line was developed by prolonged treatment with a rhenium(I) tricarbonyl isonitrile complex. The cell line was characterized and found to overexpress the ACB transporters P‐glycoprotein and ABCC1, the metallothionein MT1E, and exhibit cross‐resistance with the known anticancer agents taxol and doxorubicin.